Screen genealogies : from optical device to environmental medium - Buckley, Craig; Campe, Rüdiger; Casetti, Francesco (MediaMatters., 2019)
Against the grain of the growing literature on screens, 'Screen Genealogies' argues that the present excess of screens cannot be understood as an expansion and multiplication of the movie screen, nor of the video display. Rather, screens continually exceed the optical histories in which they are most commonly inscribed. As contemporary screens become increasingly decomposed into a distributed field of technologically interconnected surfaces and interfaces, we more readily recognize the deeper spatial and environmental interventions that have long been a property of screens. For most of its history, a screen was a filter, a divide, a shelter, or a camouflage. An intermedial genealogy stressing transformation and descent rather than origins and roots emphasizes that the understanding of the screen as optical surface was but one instance in a larger set of intersecting and competing definitions.